Impact of Decreased Estimated Glomerular Filtration Rate on Japanese Acute Stroke and Its Subtype - Katayama, Takayuki; Hasebe, Naoyuki; Matsuki, Motoki; Sawada, Jun; Nakagawa, Naoki; Kabara, Maki; Endo, Hisako; Saito, Tsukasa; Chinda, Junko; Sato, Nobuyuki (Internal Medicine, 2012)
Objective Patients with chronic kidney disease (CKD) are at a high risk for cardiovascular diseases including stroke. However, the characteristics of the stroke subtypes in patients with CKD remain to be determined. Methods We investigated the associations between stroke subtypes and estimated glomerular filtration rate (eGFR), and traditional risk factors in 451 (males, 239; mean age, 71.1 y) acute stroke patients at our hospital between 2006 and 2010. Results The stroke subtype was cardiogenic cerebral embolism in 129 (29%), cerebral hemorrhage in 104 (23%), unclassified cerebral infarction in 65 (14%), lacunar infarction in 65 (14%), subarachnoid hemorrhage in 41 (9%), atherothrombosis in 30 (7%), and transient ischemic attacks in 17 (4%). Among the 451 patients, 134 (30%) had CKD with eGFR <60 mL/min/1.73 m2. Compared with a group without CKD, mean age (75.9 vs. 69.0 years, p<0.05), the prevalence of atrial fibrillation (AF) (44% vs. 21%, p<0.01) and a history of cardiovascular disease (37% vs. 19%, p<0.01) were significantly higher in that with CKD. A comparison of stroke subtypes revealed a significantly higher incidence of cardiogenic cerebral embolism (36% vs. 26%, p<0.05) in the group with, than without CKD. Conclusion We showed the prevalence of CKD in about 30% of acute stroke patients, and those patients were older, had a significantly higher prevalence of AF and a higher rate of cardiogenic cerebral embolism compared with patients without CKD. Thus, strict control of blood pressure and management of AF should be important to prevent stroke among patients with CKD.